Analysis of regional difference decomposition of changes in energy consumption in China during 1995–2015. (15th March 2019) - Liu, Hong; Wang, Chang; Tian, Meiyu; Wen, Fenghua
Abstract: With the increase in energy consumption in China, the influential factors and contributions to such increase have received more attention. In this paper, the decomposition of energy consumption and energy intensity in China from 1995 to 2015 was conducted by using a complete decomposition model. This study focuses on regional difference, which is not in line with the existing studies. The decomposition results indicate that the economic growth has a significant driving effect on the energy consumption, while the energy intensity effect reduces the growth of the total energy consumption. The structural effect plays a negative role but has less effect on the growth of the energy consumption. The contribution rate on the growth of the energy consumption in the eastern region gradually decreases. However, in the western region it grows fast and even exceeds that of the eastern region to become the highest energy consumption area in China in 2010–2015. The energy intensity declines substantially in China. It is mainly due to the improvement of regional energy efficiency and negligible contribution from the structural effect. In conclusion, the energy consumption and energy intensity in China follow different forms in different regions. Therefore, the application of differentiated regional energy policies is preferable over a single national energy policy. Highlights: The changes in energy consumption at the regional level were decomposed. The influential factors of energy consumption variation and energy intensity variation in China was studied. The coupling relationship between China's economic growth and energy consumption growth has gradually weakened. We find that the western region become the area of China with the highest energy consumption.